Assessment of starch gelatinization by ultrasonic and calorimetric techniques - Aparicio, C. (2009)
The process of starch thermal gelatinization can be studied and monitored by employing both invasive and non-invasive techniques. In this paper, the ultrasound technique is compared with differential scanning calorimetry (DSC), a more traditional procedure. DSC is a convenient way to fulfill this objective although it is, by nature, an invasive, discontinuous and off-line technique. Among the main features of this ultrasound technique are its real-time performance and its intrinsic non-invasive character: a sample cell fitted with two piezoelectric ceramics as emitter and receptor, is used. A pulse generator and an oscilloscope are used to generate the emitted signal and to analyze the response, respectively. The procedure is tested using aqueous corn starch suspensions at two concentrations. The temperature is increased through the gelatinization interval, and the changes in ultrasound amplitude are recorded. Experimental data are in good agreement with those obtained by DSC. The progress of the gelatinization process can be followed by this method and the possibility of its use for on-line processes is considered.